Репрезентація екстралінгвальної інформації в ареальних фразеологічних словниках - Серебряк, М. (Лексикографічний бюлетень, 2011)
The article brings up a top question of the incorporation of additional extralingual
information into a dictionary entry. An analysis of some contemporary areal phraseological
dictionaries was made in order to identify the main methods of representating
extralingual information. The comparison of different types of this information presented
in the dictionaries and developed by modern linguistic science allows us to approve
the fact that not all of them are elaborated by phraseography. The author educes
the main methods of representing extralingual information in interrelation with its
typology. The basic criteria by which lexicographers may include extralingual information
in an areal phraseological dictionary are also determined. The author considers
it necessary to conduct further researchers directed to studying and developing the
methodology of representing additional information in a dictionary entry.